Proximate Analysis of the Processing of Milkfish (Chanos chanos) Cookies with the Addition of Moringa Leaves (Moringa oleifera) as Complementary Food for Stunted Children and Toddlers in Nunukan Regency, North Kalimantan - Siti Hajar; Harianti Harianti; Abdul Rahman; Renita Renita; Herlina Herlina (Jurnal Natur Indonesia, 2024)
The case of malnutrition in Indonesia is still one of the problems that the government must resolve. This is because, in recent years, cases of malnutrition among the Indonesian population, especially babies and children, have still occurred in several areas. The problem, especially stunting, in Indonesia is a national concern. The stunting reduction target for 2024 is 14%, while 2022 is still 24%. The Indonesian government has made various efforts to deal with stunting but has been unable to reduce it significantly. One of the efforts to prevent stunting is providing complementary foods for toddlers. Therefore, it is necessary to process food that has high nutritional content. One of the essential nutrients needed by the human body is protein. The urgency of this research is food processing in the form of cookies to prevent stunting, especially in Nunukan Regency, North Kalimantan Province. Processed cookies are very important for toddlers to consume to fulfill optimal nutritional requirements. This research aims to make or process cookies made from milkfish (Chanos chanos) with the addition of Moringa oleifera leaves to overcome the problem of malnutrition, especially stunting, especially in Nunukan Regency, North Kalimantan. This research aligns with the Regional Government's work program, the Regional School Children's Nutrition Program Plus (ProGasDa Plus). ProGasDa Plus is an effort to increase the nutritional intake given to students by providing nutritionally balanced additional food, accompanied by education on balanced nutrition, preventing worms, and providing supplements. Complementary foods will be analyzed proximately to see the nutritional content contained in the cookies.